Auditory aspects of acoustic neuroma dignosis - EW, Johnson (Journal of All India Institute of Speech and Hearing, 1971)
The early detection and diagnosis of an acoustic neuroma is of paramount importance to the patient with this problem. Early detection, when the tumour is still small and restricted to the internal auditory canal, simplifies the surgical procedure, shortens patient recovery time, and sometimes enables the surgeon to save the residual hearing. Since auditory symptoms are usually the first indications of a growing acoustic neuroma, an awareness of these symptoms is the key to early detection